Mitotic karyotype of the tropical freshwater crayfish Procambarus (Austrocambarus) llamasi (Decapoda: Cambaridae) - Indy, Jeane R. (Universidad de Costa Rica, 2010)
In Mexico, the biology of Procambarus has been more studied than the biology of other Cambarids because of its diversity and potential use in aquaculture. We determined the karyotype of the Mexican tropical freshwater crayfish Procambarus (Austrocambarus) llamasi from 189 metaphase spreads from gill tissues of 17 adults. They had 98-120 chromosomes (mode 2n=120 chromosomes). There are 60 pairs of monoarm, telocentric chromosomes. Sex chromosomes were not detected and we propose that the P. llamasi karyotype can be used to distinguish this species from other Mexican crayfish. Additionally, we suggest using karyological data in aquaculture and conservation biology.